2011
DOI: 10.1515/jpem.2011.086
|View full text |Cite
|
Sign up to set email alerts
|

Carotid arterial stiffness in overweight and obese Indian children

Abstract: PWV may be considered an important marker for evaluation of early functional changes of the carotid artery in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…Indeed, the author's previous reports have provided supporting evidence that the development of hypertension is associated with higher PWV in the carotid arteries of children with highest odds. 31 Mean PWV was reported as 4.6 ± 0.5 m s À1 in Australian school-children having higher body fat, 32 which is on par with children with MS in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…Indeed, the author's previous reports have provided supporting evidence that the development of hypertension is associated with higher PWV in the carotid arteries of children with highest odds. 31 Mean PWV was reported as 4.6 ± 0.5 m s À1 in Australian school-children having higher body fat, 32 which is on par with children with MS in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…Reported absolute BMI ranged from 23.9 to 37.2 (obese, youngest to eldest cohort) and 15.5 to 22.3 (controls). Only 3 studies reported BMI z-scores, [19][20][21] and 1 study used it in their regression analysis but did not report the mean values. 12 As such, we were unable to assess the linear relationship between arterial stiffness and BMI z-scores, and children were assessed based on their categorization as obese or as a healthy BMI control.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…We did not assess linear relationships between arterial stiffness and absolute BMI because of the different ages and sex of the children in the studies. Boys and girls were analyzed as 1 group in all but 1 study 20 ; thus, our analysis is not able to distinguish sex-specific differences. A summary of the characteristics for the 15 studies is provided in Table 2.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations